The Need for Global Application of the Accountability for Reasonableness Approach to Support Sustainable Outcomes: Comment on "Expanded HTA: Enhancing Fairness and Legitimacy" - Byskov, Jens (Int J Health Policy Manag, 2016)
The accountability for reasonableness (AFR) concept has been developed and discussed for over two decades. Its interpretation has been studied in several ways partly guided by the specific settings and the researchers involved. This has again influenced the development of the concept, but not led to universal application. The potential use in health technology assessments (HTAs) has recently been identified by Daniels et al as yet another excellent justification for AFR-based process guidance that refers to both qualitative and a broader participatory input for HTA, but it has raised concerns from those who primarily support the consistency and objectivity of more quantitative and reproducible evidence. With reference to studies of AFR-based interventions and the through these repeatedly documented motivation for their consolidation, we argue that it can even be unethical not to take AFR conditions beyond their still mainly formative stage and test their application within routine health systems management for their expected support to more sustainable health improvements. The ever increasing evidence and technical expertise are necessary but at times contradictory and do not in isolation lead to optimally accountable, fair and sustainable solutions. Technical experts, politicians, managers, service providers, community members, and beneficiaries each have their own values, expertise and preferences, to be considered for necessary buy in and sustainability. Legitimacy, accountability and fairness do not come about without an inclusive and agreed process guidance that can reconcile differences of opinion and indeed differences in evidence to arrive at a by all understood, accepted, but not necessarily agreed compromise in a current context - until major premises for the decision change. AFR should be widely adopted in projects and services under close monitoring and frequent reviews.